PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP MOTIVASI BELAJAR SISWA - Wahyuni, Indah; Sandi; Basri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aims to determine the effect of the Project-Based Learning (PjBL) model on students’ learning interest. The research was conducted in class XI A2 of UPT SMA Negeri 5 Bone, with a total sample of 35 students consisting of 14 male and 21 female students. The data analysis technique used was quantitative data with an ex-post facto research design and simple linear regression analysis technique. The results showed that the coefficient of determination (R Square) was 0.409, which means that the implementation of PjBL contributed 40.9% to the increase in students’ learning motivation, while 59.1% was influenced by other factors outside this study. The ANOVA test results showed an F value = 22.810 with a significance of 0.000 (<0.05), indicating that the regression model was feasible to use. Furthermore, the t-test showed that the calculated t value = 4.776 was greater than the t table value = 1.692 at a significance level of 0.05, thus the research hypothesis was accepted.